Corporate governance, economic reforms, and development : the Indian experience - Reed, Darryl; Mukherjee, Sanjoy (New Delhi ; New York : Oxford University Press, 2006)
Contributed articles.
Includes bibliographical references.
Donated By Akbar Ali Khan
Keywords: Corporate governance -- India; India -- Economic policy -- 1991-; India -- Economic conditions -- 1947-; India -- Economic conditions -- 21st century